Ganzheitliche Optimierung einer Axialkolbenpumpe durch bedarfsangepasste Entlastung tribologischer Kontakte - Haug, Stefan (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
Swash plate axial piston pumps are used in various industrial & mobile applications. An optimization of this displacement principle can be achieved by the active influence of the hydrostatic relief in tribological contacts.The approach addressed in this work is a characteristic field-based pressure control of pressure reservoirs, which can be used to adjust the degree of relief of the individual contact surfaces according to the operating point.